A szegénység Magyarországon - az arányosított deprivációs index koncepciója alapján - Spéder, Zsolt (Szociológiai Szemle, 2024)
The author summarizes the results of employing a new method, the proportional deprivation index (PDI). The novelty of the approach is the weighting of deficits in specific dimensions. The PDI takes two things into account: the lack of living condition components owing to scarcity of resources and the importance people attach to the lack of these items. According to the author’s opinion the central components of this new concept may play a part in the empirical analysis of the problem of exclusion vs. integration. On the basis of the comparison of deprivation and income poverty and the analysis of these according to various socio-economic factors the author concludes that the investigations based on disparate concepts have led to very similar results. However, certain dissimilarities are also observable, thus the simultaneous application of the concepts may/will provide a more differentiated and nuanced understanding of poverty and disadvantage.